Synthesis of TON framework molecular sieves
Patent Information
- Application Number
- JP2023548670
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-02-11
- Filing Date
- 2022-01-28
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2042-01-28
AI Technical Summary
Existing methods for synthesizing TON framework-type molecular sieves are complex and time-consuming, limiting the production of molecular sieves with unique morphology and physicochemical properties.
The use of 1,3,4-trimethylimidazolium cation as a structure directing agent and aluminosilicate starting materials allows for the synthesis of TON-type molecular sieves through a simpler and shorter process, enabling the production of molecular sieves with small crystal sizes and unique morphology.
The method enables the production of TON-type molecular sieves with improved catalytic activity in hydrocarbon conversion processes, particularly in hydroisomerization, producing increased branched hydrocarbons with enhanced catalytic performance.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an improved method for preparing molecular sieves having a TON framework structure and the use of the molecular sieves so prepared in catalytic conversion processes of hydrocarbon compounds. [Background technology]
[0002] Molecular sieve materials are classified by the Structure Commission of the International Zeolite Association according to the rules of the IUPAC Commission on Zeolite Nomenclature. Framework zeolites and other crystalline microporous crystalline materials whose structures have been established according to this classification are assigned three-letter codes and are listed in the "Atlas of Zeolite Framework Types", Revised 6th Edition, Elsevier (2007).
[0003] One of the well-known molecular sieves with well-established structures is a material called TON, which is a molecular sieve with a unique one-dimensional 10-ring channel system. Examples of TON framework molecular sieves include ISI-1, KZ-2, NU-10, Theta-1, and ZSM-22. TON framework materials are of commercial interest due to their catalytic activity in the dewaxing of paraffinic hydrocarbons.
[0004] According to the present disclosure, it has been found that the use of 1,3,4-trimethylimidazolium cation as a structure directing agent and aluminosilicate starting material allows the synthesis of TON type molecular sieves by a simpler process and with shorter heating periods than previously possible. Using these materials, TON type molecular sieves with unique morphology and physicochemical properties can be produced. In addition, it is also possible to produce TON type molecular sieves with small crystal sizes. Summary of the Invention
[0005] In a first aspect, there is provided a method for synthesizing a TON framework-type molecular sieve, the method comprising: (1) forming a reaction mixture comprising: (a) a combined source of silicon and aluminum, the combined source being an alumina-coated silica, an FAU framework-type aluminosilicate zeolite, or a mixture thereof; (b) a structure directing agent (Q) comprising a 1,3,4-trimethylimidazolium cation; (c) a source of hydroxide ions; (d) water; and (e) seed crystals; and (2) maintaining the reaction mixture under crystallization conditions sufficient to form molecular sieve crystals.
[0006] In a second embodiment, there is provided a TON framework molecular sieve which contains 1,3,4-trimethylimidazolium cations in its pores in its as-synthesized form.
[0007] In a third aspect, there is provided a process for hydroisomerization of a paraffinic hydrocarbon feedstock comprising contacting the paraffinic hydrocarbon feedstock under hydroisomerization conditions with hydrogen and a catalyst comprising a TON framework-type molecular sieve and obtaining a product having increased branched hydrocarbons relative to the hydrocarbon feedstock, the catalyst further comprising 0.01 to 10 wt. % of a precious metal. [Brief description of the drawings]
[0008] [Figure 1] 1 shows a powder X-ray diffraction (XRD) pattern of the calcined molecular sieve obtained in Example 1.
[0009] [Diagram 2] 1A and 1B show exemplary scanning electron micrograph (SEM) images of the product of Example 1 at various magnifications.
[0010] [Diagram 3] 1 shows the powder XRD pattern of the calcined molecular sieve obtained in Example 2.
[0011] [Figure 4]A and B show exemplary SEM images of the product of Example 2 at various magnifications.
[0012] [Diagram 5] 1 shows the powder XRD pattern of the calcined molecular sieve obtained in Example 3.
[0013] [Figure 6] 4A and 4B show exemplary SEM images of the product of Example 3 at various magnifications.
[0014] [Figure 7] 1 shows the powder XRD pattern of the calcined molecular sieve obtained in Example 4.
[0015] [Figure 8] 4A and 4B show exemplary SEM images of the product of Example 4 at various magnifications.
[0016] [Figure 9] 1 shows the powder XRD pattern of the calcined molecular sieve obtained in Example 5.
[0017] [Figure 10] 1 shows an exemplary SEM image of the product of Example 5.
[0018] [Figure 11] 1 shows the powder XRD pattern of the calcined molecular sieve obtained in Example 6.
[0019] [Figure 12] A and B show exemplary SEM images at various magnifications of the product of Example 6.
[0020] [Figure 13] 1 is a plot of conversion as a function of temperature for n-decane conversion for the catalyst of Example 5.
[0021] [Figure 14]1 is a plot of conversion versus yield for n-decane conversion for the catalyst of Example 5.
[0022] [Figure 15] 1 is a plot showing the distribution of methylnonane isomers as a function of conversion for n-decane conversion for the catalyst of Example 5.
[0023] [Figure 16] 1 is a plot of conversion as a function of temperature for n-decane conversion for the catalyst of Example 6.
[0024] [Figure 17] 1 is a plot of conversion versus yield for n-decane conversion for the catalyst of Example 6.
[0025] [Figure 18] 1 is a plot showing the distribution of methylnonane isomers as a function of conversion for n-decane conversion for the catalyst of Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] definition As used herein, the term "framework type" has the meaning set forth in Atlas of Zeolite Framework Types by Ch. Baerlocher, LBMcCusker and DH Olson, Elsevier, 6th revised edition, 2007.
[0027] The term "as-synthesized" refers to the molecular sieve in the form it is in after crystallization and prior to removal of the structure directing agent.
[0028] The term "Cn" hydrocarbon refers to a hydrocarbon compound having n carbon atom(s) per molecule. The term "Cn+" hydrocarbon refers to a hydrocarbon compound having n or more carbon atom(s) per molecule. The term "Cn-" hydrocarbon refers to a hydrocarbon compound having n or fewer carbon atoms per molecule.
[0029] "SiO 2 / Al 2 O 3 The term "single mole ratio" may be abbreviated as "SAR."
[0030] Molecular sieve synthesis The TON framework molecular sieve can be synthesized by (1) forming a reaction mixture containing: (a) a combined silicon and aluminum source, the combined silicon and aluminum source being an alumina-coated silica, an FAU framework-type aluminosilicate zeolite, or a mixture thereof; (b) a structure directing agent (Q) comprising a 1,3,4-trimethylimidazolium cation; (c) a source of hydroxide ions; (d) water; and (e) seed crystals; and (2) maintaining the reaction mixture under crystallization conditions sufficient to form molecular sieve crystals.
[0031] The reaction mixture was calculated in terms of molar ratio as shown in Table 1: [Table 1] (In the table, Q contains the 1,3,4-trimethylimidazolium cation) The composition may be within the range shown in
[0032] The alumina-coated silica has an SiO2 content of at least 30 (e.g., 30-170, 35-100, 50-100, 60-80, or 100-170). 2 / Al 2 O 3The alumina clad silica can be obtained from Nalco. The FAU framework type aluminosilicate zeolite can be zeolite Y. The aluminosilicate zeolite has an SiO ratio of at least 30 (e.g., 30-100, or 60-80). 2 / Al 2 O 3 The molar ratio may be 0.1 to 0.5. Examples of suitable aluminosilicate zeolites include Y zeolites CBV720, CBV760 and CBV780 available from Zeolyst International. The combined silicon and aluminum source may be used as the sole or primary source of silicon and aluminum in the reaction mixture.
[0033] The reaction mixture may contain another source of silicon. If present, suitable sources of silicon include colloidal silica, precipitated silica, fumed silica, alkali metal silicates, and tetraalkyl orthosilicates.
[0034] The source of hydroxide ions can be an alkali metal hydroxide. The alkali metal can be lithium, sodium, potassium, or a mixture thereof. However, this component can be omitted as long as the same basicity is maintained. A structure directing agent can be used to provide the hydroxide ions. When present, the alkali metal cation / SiO 2 The molar ratio may be in the range of 0.05 to 1.00 (eg, 0.05 to 0.50).
[0035] The structure directing agent (Q) has the following structure (1): [ka] The compound contains a 1,3,4-trimethylimidazolium cation represented by the formula:
[0036] Suitable sources of Q include hydroxides, chlorides, bromides, and / or salts of other quaternary ammonium compounds.
[0037] The reaction mixture also contains seed crystals, typically a TON framework molecular sieve, desirably in an amount of 0.01 to 10,000 ppm (e.g., 100 to 5000 ppm) by weight of the reaction mixture. Seeding can be advantageous to improve the selectivity of TON and / or shorten the crystallization process.
[0038] Crystallization of the desired molecular sieve from the above reaction mixture can be carried out in a suitable reaction vessel, such as, for example, a polypropylene jar or a Teflon-lined or stainless steel autoclave, under static, shaking or stirring conditions at a temperature of 120° C. to 200° C. (e.g., 135° C. to 180° C.) for a time sufficient for crystallization to occur at the temperature used, for example, about 1 to 10 days (e.g., 2 to 7 days). Crystallization is typically carried out under pressure in an autoclave such that the reaction mixture is subjected to autogenous pressure.
[0039] After the desired molecular sieve crystals are formed, the solid product can be separated from the reaction mixture by standard mechanical separation techniques such as centrifugation or filtration. The recovered crystals are washed with water and then dried for a few seconds to a few minutes (e.g., 5 seconds to 10 minutes for flash drying) or for several hours (e.g., 4 hours to 24 hours for oven drying at 75°C to 150°C) to obtain the as-synthesized molecular sieve crystals. The drying step can be carried out under vacuum or at atmospheric pressure.
[0040] As a result of the crystallization process, the recovered crystalline molecular sieve product contains within its pores at least a portion of the structure directing agent used in its synthesis.
[0041] The as-synthesized molecular sieve may be subjected to heat treatment, ozone treatment, or other treatment to remove some or all of the directing agent used in its synthesis. Removal of the directing agent may be accomplished using a heat treatment (e.g., calcination) in which the as-synthesized material is heated in an atmosphere selected from air, nitrogen, or mixtures thereof at a temperature sufficient to remove some or all of the directing agent. Pressures below atmospheric pressure may be used for the heat treatment, although atmospheric pressure is preferred for convenience. The heat treatment may be performed at a temperature of at least 370° C. (e.g., 400° C. to 700° C.) for at least 1 minute, and typically for up to 20 hours (e.g., 1 to 8 hours).
[0042] The TON type molecular sieve (from which some or all of the directing agent has been removed) may be mixed with a hydrogenation metal component. The hydrogenation metal component may be selected from molybdenum, tungsten, rhenium, nickel, cobalt, chromium, manganese, or precious metals such as platinum or palladium, capable of performing hydrogenation-dehydrogenation functions. Such hydrogenation metal components may be incorporated into the composition by one or more of the following processes: co-crystallization; ion exchange into the composition; impregnation in or physical mixing with the composition. The amount of metal may range from 0.001 to 20% by weight (0.01 to 10% by weight or 0.5 to 2.0% by weight) of the catalyst.
[0043] After the molecular sieve is synthesized, it can be prepared into a catalyst composition by combining it with another material that is resistant to the temperature and other conditions used in the organic conversion process. Such resistant material can be selected from active materials, inert materials, synthetic zeolites, naturally occurring zeolites, inorganic materials, or mixtures thereof. Examples of such resistant materials can be selected from clays, silica, titania, metal oxides such as alumina, or mixtures thereof. The inorganic materials can be naturally occurring or in the form of gelatinous precipitates or gels, including mixtures of silica and metal oxides. The use of resistant materials in combination with molecular sieves, i.e., mixed with or present during the synthesis of the as-synthesized material, where the crystals are active, tends to change the conversion and / or selectivity of the catalyst in a particular organic conversion process. The inert resistant material functions suitably as a diluent to control the amount of conversion in a given process so that the product can be obtained in an economical and orderly manner without using other means to control the reaction rate. The incorporation of these materials into naturally occurring clays (e.g., bentonite and kaolin) can improve the crush strength of the catalyst under commercial operating conditions. The inert resistant materials (i.e., clays, oxides, etc.) act as binders for the catalyst. In commercial applications, it is desirable to prevent the catalyst from breaking down into powder-like materials, so a catalyst with good crush strength can be beneficial.
[0044] Naturally occurring clays which may be complexed with the molecular sieves include the montmorillonite and kaolin families, including the sub-bentonites and kaolins commonly known as Dixie clays, McNamee clays, Georgia clays and Florida clays, or others whose major mineral components are halloysite, kaolinite, dickite, nacrite or anoxicite. Such clays may be used in their original as-mined state or may first be calcined, acid treated or chemically modified.
[0045] Binders useful for compositing with molecular sieves also include inorganic oxides selected from silica, zirconia, titania, magnesia, beryllia, alumina, or mixtures thereof.
[0046] In addition to the aforementioned materials, the molecular sieves may be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, as well as ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia.
[0047] The relative proportions of molecular sieve and inorganic oxide matrix can vary widely, with the molecular sieve content ranging from 1 to 95 weight percent (eg, 20 to 90 weight percent) of the composite.
[0048] The catalyst is applied in a conventional manner, for example in the form of spheres or extrudates.
[0049] Characterization of molecular sieves In their as-synthesized anhydrous form, the molecular sieves have the following molar ratios as shown in Table 2: [Table 2] (In the table, Q contains the 1,3,4-trimethylimidazolium cation) The composition may be within the ranges shown in
[0050] TON framework molecular sieves prepared as described herein may have small crystal sizes. The crystal size is based on individual crystals (including twins), but does not include crystal aggregates. The crystal size is the length of the longest diagonal of a three-dimensional crystal. Direct measurements of crystal size can be made using microscopy techniques such as SEM and TEM. For example, measurements by SEM involve examining the morphology of the material at high magnification (usually 1000x to 10,000x). SEM techniques can be performed by dispersing a representative portion of the molecular sieve powder on a suitable specimen stage so that the individual particles are reasonably evenly spread across the field of view at 1000x to 10,000x magnification. From this population, a statistically significant sample of random individual crystals (e.g., 50-200) is examined and the longest diagonal of the individual crystals is measured and recorded. (Particles that are clearly large polycrystalline aggregates should not be included in the measurements). Based on these measurements, the arithmetic mean of the crystal size of the sample is calculated.
[0051] The TON framework molecular sieves synthesized as described herein are characterized by their powder X-ray diffraction (XRD) patterns. Powder XRD patterns representative of TON framework molecular sieves can be found in "Collection of Simulated XRD Powder Patterns for Zeolites" by MM J Treacy and JB Higgins (Elsevier, 5th revised edition, 2007).
[0052] The X-ray diffraction data reported herein were collected by standard techniques using CuKα radiation. Slight variations in the diffraction patterns may result from variations in the molar ratios of framework species in a particular sample resulting in changes in lattice constants. In addition, sufficiently small crystals affect peak shape and intensity, resulting in significantly broadened peaks. Slight variations in the diffraction patterns may also result from variations in the organic compounds used in the preparation. Calcination may also result in slight shifts in the XRD patterns. Despite these slight variations, the basic crystal lattice structure remains unchanged.
[0053] Hydroisomerization of Paraffinic Hydrocarbon Feedstocks The molecular sieve is suitable for use as a catalyst in the hydroisomerization of a paraffinic hydrocarbon feedstock by contacting the catalyst with hydrogen under hydroisomerization conditions to produce a product having increased branched hydrocarbons relative to the hydrocarbon feedstock.
[0054] Hydroisomerization conditions include a temperature of 200°C to 450°C (e.g., 250°C to 400°C), a pressure of 0.5 to 20 MPa (e.g., 1 to 15 MPa), and a reaction time of 0.1 to 10 h. -1 (For example, 0.5 to 5 hours -1 ) liquid hourly space velocity, and 35.6 to 1781 Nm 3 / m 3 (For example, 890~1424Nm 3 / m 3 ) hydrogen circulation rate.
[0055] When the hydrocarbon feedstock includes n-C8+ hydrocarbons (e.g., n-C10+ hydrocarbons, or n-C15+ hydrocarbons), the hydrocarbon feedstock is not limited to a particular type. More specifically, examples of such hydrocarbon feedstocks include relatively light distillation fractions such as kerosene and jet fuel, all kinds of crude oil, atmospheric distillation residues (atmospheric residues), vacuum tower residues, vacuum distillation residues (vacuum residues), recycle feedstocks, synthetic crude oils (e.g., shale oil, tar oil, etc.), gas oils, vacuum gas oils, waxy bottom oils, and high boiling feedstocks such as fuel or wax fractions derived from Fischer-Tropsch synthetic oils, as well as other heavy oils. EXAMPLES
[0056] The following illustrative examples are intended to be non-limiting.
[0057] Example 1 In a 23 mL Teflon autoclave, 3.96 g of 1,3,4-trimethylimidazolium hydroxide in water (0.98 mmol OH) was added. -1.0 g of CBV780 Y zeolite (SAR=80) was then added followed by zeolite TON seed crystals and mixed well. The closed autoclave was heated at 170°C for 3 days with rotation at 43 rpm. The material was recovered by filtration, washed with copious amounts of water and finally air dried at 85°C.
[0058] The material was calcined in air by placing a thin layer of material in a calcination dish and heating it in a muffle furnace from room temperature to 120°C at a rate of 1°C / min and holding at 120°C for 2 hours. The temperature was then increased at a rate of 1°C / min to 540°C and held at 540°C for 5 hours. The temperature was again increased at 1°C / min to 595°C and held at 595°C for 5 hours. The material was then allowed to cool to room temperature.
[0059] The powder XRD pattern of the calcined material is shown in Figure 1, which indicates that the material is a TON framework zeolite. Figure 2A and B show exemplary SEM images of the product at various magnifications. As shown, the crystals have a columnar morphology with an average length of more than 1 μm, an average width of about 0.5 μm, and an average thickness of less than 0.1 μm.
[0060] Example 2 In a 23 mL Teflon autoclave, 0.72 g of 1,3,4-trimethylimidazolium hydroxide in water (0.98 mmol OH) was added. - / g) with 0.17 g of LiOH H 2 The mixture was mixed with 7.0 g of DI water and 7.22 g of deionized water. Then, 4.0 g of alumina coated silica (SAR=100, solids 26.5%, Nalco) was added followed by zeolite TON seeds and mixed well. The closed autoclave was heated at 170° C. for 3 days while rotating at 43 rpm. The material was recovered by filtration, washed with copious amounts of water and finally air dried at 85° C.
[0061] The as-synthesized material was calcined according to the method described in Example 1.
[0062] The powder XRD pattern of the calcined material is shown in Figure 3, which indicates that the material is a TON framework zeolite. Figure 4A and B show exemplary SEM images of the product at various magnifications. As shown, the crystals were in the form of bundled needles with an average length of more than 1 μm and an average thickness of less than 0.1 nm.
[0063] Example 3 In a 23 mL Teflon autoclave, 0.72 g of 1,3,4-trimethylimidazolium hydroxide in water (0.98 mmol OH) was added. - / g) with 0.096 g of LiOH H 2 The mixture was mixed with 1.76 g of 1M KOH and 5.54 g of deionized water. Then, 4.0 g of alumina-coated silica (SAR=100, solids 26.5%, Nalco) was added followed by zeolite TON seeds and mixed well. The closed autoclave was heated at 170° C. for 3 days while rotating at 43 rpm. The material was collected by filtration, washed with copious amounts of water and finally air-dried at 85° C.
[0064] The as-synthesized material was calcined according to the method described in Example 1.
[0065] The powder XRD pattern of the calcined material is shown in Figure 5, which indicates that the material is a TON framework zeolite. Figure 6A and B show exemplary SEM images of the product at various magnifications. As shown, the crystals were in the form of columnar bundled needles with an average length of more than 1 μm, an average width of about 0.1 μm, and an average thickness of less than 100 nm.
[0066] Example 4 In a 23 mL Teflon autoclave, 1.91 g of 1,3,4-trimethylimidazolium hydroxide in water (0.98 mmol OH) was added. - / g) with 0.085 g of LiOH H 2The mixture was mixed with 3.0 and 3.42 g of deionized water. Then, 1.0 g of CBV780 Y zeolite (SAR=80) was added followed by zeolite TON seed crystals and mixed well. The closed autoclave was heated at 150° C. for 3 days while rotating at 43 rpm. The material was recovered by filtration, washed with copious amounts of water and finally air-dried at 85° C.
[0067] The as-synthesized material was calcined according to the method described in Example 1.
[0068] The powder XRD pattern of the calcined material is shown in Figure 7, which indicates that the material is a TON framework zeolite. Figure 8, A and B, show exemplary SEM images of the product at various magnifications. As shown, the crystals were in the form of irregularly shaped platelets with average dimensions less than 1 μm x 1 μm and an average thickness less than 50 nm.
[0069] Example 5 In a 125 mL Teflon autoclave, 5.38 g of 1,3,4-trimethylimidazolium hydroxide in water (0.88 mmol OH) was added. - 100g of 1M KOH and 21.2g of deionized water were mixed. Then, 21.0g of alumina-coated silica (SAR=35; solids 24.5%, Nalco) was added, followed by 7.02g of LUDOX® AS-30 colloidal silica, followed by zeolite TON seeds and mixed well. The closed autoclave was heated at 175°C for 2 days with rotation at 43 rpm. The material was collected by filtration, washed with copious amounts of water and finally air-dried at 85°C.
[0070] The as-synthesized material was calcined according to the method described in Example 1.
[0071] The powder XRD pattern of the calcined material is shown in Figure 9, which indicates that the material is a TON framework zeolite. Figure 10 shows an exemplary SEM image of the product. As shown, the crystals were in the form of fibrous bundle needles with small crystal size.
[0072] The calcined material was then converted to the ammonium form by heating in ammonium nitrate solution (typically H 2 1 g NH in 10 mL 4 NO 3 / 1g zeolite, 85°C for at least 3 hours). The material was then filtered. This was repeated twice for a total of three exchanges. Finally, the material was washed with deionized water until the conductivity was less than 100 μS / cm and air-dried at 85°C.
[0073] The acid site density was characterized using n-propylamine temperature programmed desorption (TPD) and found to be 522 μmol H + / g.
[0074] Nitrogen pore volume is 0.095 cm 3 / g (t-plot analysis) and the BET surface area was found to be 232.6 m 2 / g.
[0075] The SAR of the material was found to be 44.7 by inductively coupled plasma mass spectrometry (ICP-MS).
[0076] To exchange for palladium to 0.5 wt% Pd, 1.6 g of NH 4 + Form the material in 15.3 g of deionized water and 7.0 g of 0.156 N NH 4 The OH solution was mixed with 1.6 g of palladium solution, which was made up of 21 g of deionized water and 3 g of 0.148 N NH 4 0.36 g of Pd(NH 3 ) 4 (NO 3 ) 2The Pd form was prepared by mixing the above ingredients. The pH was then checked and adjusted to 10, if necessary, by dropwise addition of concentrated ammonium hydroxide until a pH of 10 was reached. After standing at room temperature for 3 days, the pH was checked again and readjusted to 10, if necessary, and allowed to stand for another day. The material was recovered by filtration, washed with deionized water, and air-dried at 85°C overnight. The Pd form material was calcined in dry air by heating at 1°C / min to 120°C and holding at 120°C for 180 minutes, then heating at 1°C / min to 482°C and holding at 482°C for 180 minutes. Finally, the material was pelletized at 5 kpsi, crushed, and sieved to 20-40 mesh.
[0077] Example 6 In a 125 mL Teflon autoclave, 5.37 g of 1,3,4-trimethylimidazolium hydroxide in water (0.88 mmol OH) was added. - 10.0 g of 1M KOH and 20.1 g of DI water were mixed. 29.0 g of alumina coated silica (SAR=80; solids 26.9%, Nalco) was then added followed by zeolite TON seeds and mixed well. The closed autoclave was rotated at 43 rpm and heated at 175°C for 2 days. The material was recovered by filtration, washed with copious amounts of water and finally air dried at 85°C.
[0078] The material was calcined and converted to the ammonium form according to the method described in Example 5.
[0079] The powder XRD pattern of the calcined material is shown in Figure 11, which indicates that the material is a TON framework zeolite. Figure 12A and B show exemplary SEM images of the product at various magnifications. As shown, the crystals have a slightly lamellar morphology with very small crystal sizes.
[0080] The acid site density was characterized using n-propylamine TPD and found to be 340 μmol H + / g.
[0081] Nitrogen micropore volume is 0.10 cm 3 / g (t-plot analysis) and the BET surface area was found to be 240.1 m 2 / g.
[0082] The SAR of the material was found to be 70.1 by ICP-MS.
[0083] Exchange into 0.5 wt % Pd was carried out according to the method described in Example 5.
[0084] Example 7 Hydrogen conversion rate of n-hexadecane 0.5 g of the palladium-exchanged sample was loaded into the center of a 23 inch long by 0.25 inch OD stainless steel reaction tube packed with alundum upstream of the catalyst and the feed was preheated (total pressure 1200 psig; downflow hydrogen rate 160 mL / min; downflow liquid feed rate 1 mL / hr, measured at 1 atm and 25°C). All materials were first reduced in flowing hydrogen at about 315°C for 1 hour. Products were analyzed by on-line capillary gas chromatography (GC) once every 30 minutes. Raw data from the GC was collected by an automated data acquisition / processing system and the hydrocarbon conversion was calculated from the raw data.
[0085] Conversion was defined as the amount of n-hexadecane that reacted to produce other products, including the iso-C16 isomer. Yields were expressed as the weight percent of products other than n-C16 and included the output product iso-C16. Results at 96% conversion are reported in Table 3. [Table 3]
[0086] Example 8 Hydrogen Conversion of n-Decane For catalytic testing, 0.5 g of palladium catalyst (weight of anhydrous sample determined by thermogravimetric analysis at 600°C) was loaded into the center of a 23 inch long by 0.25 inch OD stainless steel reaction tube with alundum packed upstream of the catalyst and preheated feed (total pressure 1200 psig; downflow hydrogen rate 12.5 mL / min; downflow liquid feed rate 1 mL / hr, measured at 1 atm and 25°C). The catalyst was first reduced in flowing hydrogen at 315°C for 1 hour. The reaction was carried out at temperatures between 230°C and 310°C. Products were analyzed by on-line capillary GC approximately once every 60 minutes. Raw data from the GC was collected by an automated data acquisition / processing system, and the hydrocarbon conversion was calculated from the raw data. Conversion was defined as the mole percent amount of n-decane that reacted to produce other products (including iso-C10). The yield of iso-C10 is expressed as the mole percent of products other than n-decane. The yield of cracked products (less than C10) is expressed as the mole percent of n-decane converted to cracked products. The results are shown in Figures 13 to 18, and the key catalyst performance indicators are shown in Table 4.
[0087] Degenerative Constraint Index (CI * ) was calculated as the ratio of 2-methylnonane to 5-methylnonane at a total isomeric yield of about 5% and is shown in Table 4. [Table 4]
Claims
1. A method for synthesizing a TON framework molecular sieve, comprising: (1) The following: (a) a combined silicon and aluminum source, said combined silicon and aluminum source being an alumina-coated silica, an aluminosilicate zeolite of the FAU framework type, or a mixture thereof; (b) a structure directing agent (Q) containing a 1,3,4-trimethylimidazolium cation; (c) a source of hydroxide ions; (d) water; and (e) a seed crystal comprising a TON framework molecular sieve; forming a reaction mixture comprising: (2) maintaining the reaction mixture under crystallization conditions sufficient to form crystals of the molecular sieve, The reaction mixture contains, in molar ratio terms, the following: 【Table 1A】 The method according to claim 1, wherein the composition is as follows:
2. The reaction mixture contains, in molar ratio terms, the following: 【Table 1B】 The method of claim 1 having a composition as follows:
3. 2. The method of claim 1, wherein the FAU framework-type aluminosilicate zeolite is zeolite Y.
4. The method of claim 1 , wherein the source of hydroxide ions comprises an alkali metal hydroxide.
5. 5. The method of claim 4, wherein the alkali metal is lithium, sodium, potassium, or a mixture thereof.
6. Alkali metal cation / SiO 2 The method according to claim 5, wherein the molar ratio of is in the range of 0.1 to 1.
0.
7. 10. The method of claim 1, wherein the reaction mixture comprises from 0.01 ppm to 10,000 ppm by weight of seed crystals.
8. The method of claim 1 , wherein the reaction mixture further comprises another silicon source.
9. 9. The method of claim 8, wherein the other silicon source comprises colloidal silica, precipitated silica, fumed silica, an alkali metal silicate, a tetraalkyl orthosilicate, or a mixture thereof.
10. 10. The method of claim 1, wherein the crystallization conditions include a temperature of from 125° C. to 200° C. and a time of from 1 day to 10 days.
11. The method of claim 1, wherein the as-synthesized TON framework molecular sieve is subjected to a heat treatment to remove some or all of the structure directing agent.
12. The method of claim 11, wherein the TON framework molecular sieve is mixed with a hydrogenation metal component.